Impact Analysis of the Tiered Referral System Implementation on Outpatient Visit Reduction at Dr. Ferdinand Lumban Tobing Hospital, Sibolga - Syuryanty Sidabutar; Karnirius Harefa; Tati Murni Karo-Karo (JURNAL KESMAS DAN GIZI (JKG), 2026)
Health is a fundamental right and an important indicator of a country’s development. The Indonesian government, through the National Health Insurance (JKN) program administered by BPJS Kesehatan, has implemented a tiered referral system to improve the efficiency and quality of healthcare services. This study aims to analyze the impact of implementing the tiered referral system on outpatient visits at RSUD Dr. Ferdinand Lumban Tobing Sibolga, as well as its implications for hospital services, resources, and management. This study employed a quantitative analytic comparative design using a cross-sectional approach combined with retrospective secondary data analysis from 2013 to 2023. The sample included all outpatient visit data using total sampling. Data analysis was conducted using univariate analysis to describe data distribution and bivariate analysis with a paired t-test to examine differences in visits before and after the implementation of the tiered referral system. The results showed a decrease in outpatient visits by 11.31% (from 74,310 to 65,902 visits), with most mild cases being handled at primary healthcare facilities (FKTP), while the hospital managed more complex cases. Hospital revenue remained stable due to an increase in specialized services. Implementation challenges included inappropriate referrals, patient perceptions of complicated referral procedures, long waiting times, and differences in service between JKN and non-JKN patients, which affected patient satisfaction and healthcare-seeking behavior. In conclusion, the tiered referral system has multidimensional impacts on hospitals and patients. Strengthening coordination among healthcare facilities, enhancing the capacity of healthcare workers, and providing education and socialization to the community are necessary to improve patient understanding, satisfaction, and the effective utilization of healthcare services.